Surface‐Engineered Homostructure for Enhancing Proton Transport. Issue 1 (8th December 2021) - Wang, Faze; Hu, Enyi; Wu, Hao; Yousaf, Muhammad; Jiang, Zheng; Fang, Li; Wang, Jun; Kim, Jung‐Sik; Zhu, Bin
Abstract: Ultra‐wide bandgap semiconductor samarium oxide attracts great interest because of its high stability and electronic properties. However, the ionic transport properties of Sm2 O3 have rarely been studied. In this work, Ni doping is proposed to be used for electronic structure engineering of Sm2 O3 . The formation of Ni‐doping defects lowers the Fermi level to induce a local electric field, which greatly enhances the proton transport at the surface. Furthermore, ascribed to surface modification, the high concentration of vacancies and lattice disorder on the surface layer promote proton transport. A high‐performance of 1438 mW cm –2 and ionic conductivity of 0.34 S cm –1 at 550 °C have been achieved using 3% mol Ni doped Sm2 O3 as electrolyte for fuel cells. The well‐dispersed Ni doped surface in Sm2 O3 builds up continuous surfaces as proton channels for high‐speed transport. In this work, a new methodology is presented to develop high‐performance, low‐temperature ceramic fuel cells. Abstract : An advanced Sm2 O3 /Ni‐Sm2 O3 core‐shell homostructure material with high proton conductivity is developed for a low‐temperature solid oxide fuel cell. The local electrical field created by the interface confines the proton migration on the surface layer with accelerated ion transmission and promoted proton diffusion kinetics. This presents a new understanding for proton transport in rare‐earth metal oxides semiconductor materials.